2013
DOI: 10.1037/a0033345
|View full text |Cite
|
Sign up to set email alerts
|

Does communicating disappointment in negotiations help or hurt? Solving an apparent inconsistency in the social-functional approach to emotions.

Abstract: On the basis of a social-functional approach to emotion, scholars have argued that expressing disappointment in negotiations communicates weakness, which may evoke exploitation. Yet, it is also argued that communicating disappointment serves as a call for help, which may elicit generous offers. Our goal was to resolve this apparent inconsistency. We develop the argument that communicating disappointment elicits generous offers when it evokes guilt in the target, but elicits low offers when it does not. In 4 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 102 publications
(286 reference statements)
7
35
0
Order By: Relevance
“…Interestingly, the expression of disappointment did increase self-reported intentions to help the expresser. This finding is in line with research on prosocial behavior (Van Doorn et al, 2015) and negotiation (Van Kleef et al, 2006; Lelieveld et al, 2013), which also yielded evidence that expressions of disappointment can elicit cooperative behavior. Whether disappointment reliably yields a social appraisal that someone should be helped, however, is a question for further research.…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the expression of disappointment did increase self-reported intentions to help the expresser. This finding is in line with research on prosocial behavior (Van Doorn et al, 2015) and negotiation (Van Kleef et al, 2006; Lelieveld et al, 2013), which also yielded evidence that expressions of disappointment can elicit cooperative behavior. Whether disappointment reliably yields a social appraisal that someone should be helped, however, is a question for further research.…”
Section: Discussionsupporting
confidence: 89%
“…Specifically, we showed that communicating intergroup disappointment can potentially stimulate collective guilt and action in the context of an intractable conflict. Lelieveld et al (2013) previously demonstrated that disappointment expressions by ingroup members increased guilt in negotiations, whereas if the expresser was an outgroup member, disappointment did not induce individual guilt in the observer in the interpersonal conflict. Our work expands on this by demonstrating for the first time that expressions of outgroup disappointment evoke collective guilt and collective action specifically among ingroup members who do not justify the ingroup transgression, even in a severe type of intergroup conflict.…”
Section: Discussionmentioning
confidence: 95%
“…Previous work using this perspective has mostly focused on expressions of emotions in the interpersonal context (e.g. Van Kleef, De Dreu, & Manstead, 2004a;Van Kleef, De Dreu, & Manstead, 2006) and surprisingly little attention has been given to the role of emotional expressions in the intergroup context (for some exceptions, see Kamans et al, 2014;Lelieveld et al, 2013;de Vos, Van Zomeren, Gordijn, & Postmes, 2013;de Vos, Van Zomeren, Gordjin, & Postmes, 2016). Indeed, we are not aware of any study that investigates whether the communication of intergroup disappointment evokes collective guilt and collective action in the intergroup realm.…”
Section: Social Function Of Disappointment In Intergroup Conflictmentioning
confidence: 93%
See 2 more Smart Citations